Effect of nanostructured lipid carrier containing chitosan on free cells and biofilm of Escherichia coli - Osungunna, Michael Oluwole (2019)
Urinary tract infection (UTI) is the most common hospital acquired pathological process and indwelling urinary catheters increase the risk of bacteriuria, which can progress to a serious condition. This infection usually follows formation of biofilm on both the internal and external catheter surface. The uropathogenic bacteria Escherichia coli is the most common infecting microorganism on catheter and its biofilms have been studied as a platform to select strategies to control UTIs. The present study examined whether a nano delivery system containing chitosan affected the growth of uropathogenic biofilms of E. coli. This work was divided in two stages, the first involved comparing adhesion surfaces most used in in vitro biofilm models and the second evaluated the susceptibility of free cells and biofilm of E. coli to a nanostructured lipid carrier coated with chitosan (NLC-chitosan). Thus, E. coli biofilms were formed on catheter, glass slides or tissue culture plates for 5 days and the composition of biofilm was evaluated. In the second stage of the work, NLC-chitosan was prepared using the emulsion and sonication method, and further characterized with respect to particle size, polydispersity index, and zeta potential. After determining the minimum inhibitory (MIC) and bactericidal concentrations (MBC), E. coli biofilms were grown on catheter specimens. At the 48, 72, 96, and 120 hours of growth, biofilms were exposed to 0.9% NaCl solution (negative control), 0.12% chlorhexidine solution (positive control), or NLC-chitosan (final chitosan concentration of 0.28%). After 24 hours of treatment, the biofilms were collected to analyze their bacterial viability. Data were statistically analyzed by Tukey-Kramer or Tukey test with a level of significance of 5%. Bacterial colony viability was higher in catheter compared to glass slides or plates (p<0.05) and the lowest bacterial count was observed for glass slide (p<0.05). Although concentrations of carbohydrate were lower in biofilm formed on catheter (p<0.05), no differences were observed between catheter and plate (p>0.05) as well as glass slides and plate (p>0.05) for protein quantification. Regarding second work stage, NLC-chitosan preparation had bimodal particle size distribution with mean size of 292.9 ± 2.5 nm and polydispersity index of 0.24 ± 0.03, and positive zeta potential (+19.1 ± 0.2) indicating the nanoparticle coating by chitosan. Analysis of MIC and MBC values revealed that formulation inhibited bacterial growth and exerted bactericidal action at concentrations 100 times higher than those required for chlorhexidine digluconate (positive control). Compared with the control groups, NLC-chitosan affected bacterial colony viability of biofilms at all ages studied (p<0.05). The results suggest that catheter is a proper surface to study E. coli biofilm compared to either glass slides or polystyrene plates. In addition, both free cells and biofilms of E. coli were significantly affected by NLC-chitosan, which can be a feasible approach for studies using uropathogenic bacteria. In future, urinary catheter can be used as model to study simulated UTIs, using mixed populations of bacteria, and the effect of NLC-chitosan or its association with other antimicrobial agents evaluated.